Harmonization of corporate taxes in the EC : proceedings of a seminar held in Florence, Italy, in 1993 during the 47th Congress of the International Fiscal Association.: proceedings of a seminar held in Florence, Italy, in 1993 during the 47th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available